Pengurangan Ketimpangan Melalui Penciptaan Lapangan Pekerjaan Dan Program Pemberdayaan Masyarakat Di Kampung Nelayang Seberang Sebagai Upaya Pengimplementasian SDGS Di Tingkat Lokal - Helga Yohana Simatupang; Dhilva Ananda (Politeknik Kampar, 2023)
The Sustainable Development Goals (SDGs) are theoretically international action plans adopted by world leaders, including Indonesia, with the intention of eradicating poverty, reducing inequality, and preserving the environment. The 17 Goals and 169 Targets in the SDGs are supposed to be accomplished by 2030. It is thought necessary to address the gaps and various levels of awareness of the SDGs with a new communication strategy or campaign. The growth of information and communication technologies, demographic trends, and political-economic realities are all taken into consideration while developing a communication strategy to address Indonesia's SDGs collaboration challenges. One of the strategies is to combine field study and dissemination methodologies through lecturer’s Community Service. The targeted audiences of this activity are residents of Kampung Nelayan Seberang in Medan Belawan District. It is important to raise public awareness of the local level implementation of the SDGs in order to alleviate social inequality through community empowerment programs and job creation for coastal communities. The evaluation's findings indicate that this service activity has increased public awareness of the 17 goals of SDGs, which can be expanded upon and applied to the lives of the Kampung Nelayan Seberang community. The method of delivering material is in the form of seminars which are conducted in the community meeting hall. Furthermore, lecturers, students, and members of the local community collaborate to conduct field assessments to determine the actual conditions at the site of the activity and map the most urgent needs in the community.